Determinant factors of successful internal communications at Perbadanan Usahawan Nasional Berhad (PUNB)/Nor Muzalifah Samean - Samean, Nor Muzalifah (Faculty of Business and Management, 2010)
The purpose of the research is to study the determinant factors of successful internal communications at Perbadanan Usahawan Nasional Berhad (PUNB). In this study, the dependent variable is successful internal communications. While the independent variables for the research are timely, clear, accurate, pertinent and credible. The study conducted at Perbadanan Usahawan Nasional Berhad (PUNB), located at Kuala Lumpur Sentral. 85 of the staff are selected to be the respondents of this research. From the findings, 39 of the respondents is Male and another 46 respondents is Female. 64.7% of the respondents are graduates with Degree and majority of the staff at PUNB is Executive. Based the findings, there is a significant relationship between independent variables and dependent variable. Besides, from the findings the researcher finds that the factor of credible is the most factor influence to the successful internal communications at PUNB. The finding is based from Beta Standardized Coefficient which is the result is 0.735. From the research been made, the researcher finds that the reliability analysis is 0.966 close to 1. This represents that the questionnaire is free from error. The R square of the research conducted is 73.4% is explaining by the independent variables.